Open Secrets - Munro, Alice, 1931- (London Vintage Books, 1995)
**Winner of the Nobel Prize in Literature**Ranging from the 1850s through two world wars to the present, and from Canada to Brisbane, the Balkans and the Somme, these dazzling stories reveal the secrets of unconventional women who refuse to be contained.
Keywords: Canada -- Women--Social life and customs -- Short stories, Canadian